Preconcentration with 1-Nitroso-2-naphthol Complexes on Dowex MWC-1 Resin: Determination of Cu and Zn at Trace Level in Drinking Water Samples by ICP-AES - A. Demir Mulazimoglu; I. E. Mulazimoglu; E. Ozkan (E-Journal of Chemistry)
In this study, copper(II) and zinc(II) were quantitatively determined in drinking water using ICP-AES after preconcentration. For this purpose, the water samples were treated with 1-nitroso-2-naphthol to form metal complexes on Dowex MWC-1 resin. Prior to the sorption process, the column was treated with a chelating resin Dowex MWC-1 and the column was prepared by passing buffer solution at different pH values. These columns were used for the transportation of water samples through the resin at the flow rate of 2.00 mL min-1. The effluents were then analyzed by ICP-AES using standard addition method. The effect of pH, amount of resin, ligand concentration and eluent type were investigated. The detection limit for Cu(II) and Zn(II) were found to be 2.78 μg L-1and 6.34 μg L-1 respectively (RSD.’s <%5).it would be concluded that the determination of copper(II) and zinc(II) in drinking water was simple, fast and repliable using this technique.